2011
DOI: 10.5657/fas.2011.0317
|View full text |Cite
|
Sign up to set email alerts
|

Development of Economical Fertilizer-Based Media for Mass Culturing of Nannochloropsis oceanica

Abstract: This study was conducted to develop economical agricultural fertilizer media for the mass culturing of Nannochloropsis oceanica. Specific growth rates of N. oceanica cultured with differing concentrations of commercial compounds, urea fertilizers, and trace elements (Zn, Cu, Co, Mo) were compared with the growth rate in f/2 medium. Among the various added trace elements, CuSO 4 ‧5H 2 O was most effective for high growth of N. oceanica. The main nitrogen source in the agricultural fertilizers was ammonium, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our suggestions were in agreement with Guzman-Murillo et al who suggested that, CAGF media may be used to improve the biochemical composition of microalgae for the purposes of aquaculture, production of bioactive materials and biotechnology. Bae and Hur, (2011) found that the growth of N. oceanica cultured on fertilizer medium was similar to that of N. oceanica cultured in F/2 medium. On the other hand, our results disagree with Simental and Sanchez-Saavedra (2003) [22] who pointed that, comparing to F/2 medium, the using of liquid CAGF did not achieve any significant differences in cell concentration and growth rate of Navicula incerta, Nitzschia thermalis and Nitzschia laevis.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our suggestions were in agreement with Guzman-Murillo et al who suggested that, CAGF media may be used to improve the biochemical composition of microalgae for the purposes of aquaculture, production of bioactive materials and biotechnology. Bae and Hur, (2011) found that the growth of N. oceanica cultured on fertilizer medium was similar to that of N. oceanica cultured in F/2 medium. On the other hand, our results disagree with Simental and Sanchez-Saavedra (2003) [22] who pointed that, comparing to F/2 medium, the using of liquid CAGF did not achieve any significant differences in cell concentration and growth rate of Navicula incerta, Nitzschia thermalis and Nitzschia laevis.…”
Section: Discussionmentioning
confidence: 71%
“…However, the effect of nonconventional media prepared from CAGF on microalgae growth [2,18,19] and biochemical composition [20,21] were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and nutritional composition of M. subterraneus and N. oceanica according to trophic culture method Culture of algae M. subterraneus (KMMCC-1348, 6.76 ± 0.61 µm (major axis), 3.66 ± 0.55 µm (minor axis)) and N. oceanica (KMMCC-359, diameter: 2.64 ± 0.41 µm), received from the Korea Marine Microalgae Culture Center (KMMCC), Pukyong National University, were cultured for this study. Jaworski's medium (JM) (Thompson et al 1988) for M. subterraneus and f/2 medium (Guillard and Ryther 1962) for N. oceanica were used, and the two species were cultured at 25 o C with continuous light of 80 µmol photons m −2 s −1 (Bae and Hur 2011a;Jo 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The use of agricultural fertilizers as ingredients in culture medium for the growth of Trichoderma spp. is uncommon, but they have been used in microalgae scaling processes [17,18]. In Trichoderma, nitrogen fertilizers stimulate growth and conidia production and, in large amounts may have a synergistic effect on biocontrol effectiveness [19].…”
Section: Introductionmentioning
confidence: 99%